Effort to Fulfill Female Convicts’ Rights to Health and Clothing at Sigli Class Iib Correctional Facility for Women - Mustafa Hasan (Jurnal Penelitian Hukum De Jure, 2021)
Article 14 Paragraph (1) letter d of Law Number 12 Year 1995 concerning Corrections. The right to health services and the right to adequate clothing are often neglected and have not been fully implemented properly. The purpose of this research is to find out and explain the fulfilment of the rights to health and clothing of female convicts at the Sigli Class IIB Correctional Facility for Women. This research method is an empirical juridical method by using a descriptive analysis approach. The results of the study showed that the fulfilment of the rights to health and clothing has not been implemented optimally pursuant to what is mandated by law, and Article 14 Paragraph (2) of Government Regulation Number 32 Year 1999 concerning Terms and Procedures for the Implementation of the Rights of Correctional Inmates. To ensure optimal health services, at least one doctor must be provided. However, in this case it is not yet available at the Sigli Class IIB Correctional Facility for Women. One of the efforts made by the correctional facility is to collaborate with the local government to check the health of correctional inmates at least 1 (one) time in 1 (one) month and it is recorded in a health card. As for clothing need, it has been given partly to female convicts, but has not been given in full due to the lack of budget given to the Sigli Correctional Facility for Women. The responsibility of the state is to finance the fulfilment of the rights that have been regulated in the law, for example in the provision of health and clothing rights in a Correctional Facility, the facility shall have at least a doctor, nurses, clinics and medicines sufficient to support health facility in the Correctional Facility or Detention Center.